Performance Analysis Using the Balanced Scorecard at Sultan Muhammad Jamaludin I Regional General Hospital in Kayong Utara Regency - Yunanda Febriyanti; Fuad Ramdhan Ryanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the performance of RSUD Sultan Muhammad Jamaludin I using the Balanced Scorecard from the financial, customer, internal business process, and learning and growth perspectives for the 2021–2024 period based on available financial and operational data. The method used is descriptive quantitative. Primary data were collected through questionnaires distributed to 50 patients and employees via Google Forms, while secondary data consisted of financial/operational reports, revenue details, medical records, and staffing data. The research instruments were tested and declared valid and reliable, thus suitable for use as data collection tools. The results show that hospital performance varies across the Balanced Scorecard perspectives. From the financial perspective, performance has not been fully optimal due to an imbalance between expenditure realization and cost efficiency, although revenue achievement was able to exceed the target. From the customer perspective, performance is classified as good, indicated by the ability to retain and attract patients as well as a customer satisfaction index of 83,04% which is in the good category. From the internal business process perspective, the utilization of inpatient facilities has not been optimal and has not met service standards, although clinical quality indicators are relatively good. Meanwhile, the learning and growth perspective shows positive performance reflected in high employee retention, a tendency toward increased productivity, and an employee satisfaction index of 85,9%. These findings confirm that the Balanced Scorecard is able to provide a more comprehensive picture of hospital performance through the integration of financial and non-financial aspects.